Platinum-based Chemotherapy in Primary Advanced Seminoma—a Retrospective Analysis: Treatment Results at the Northern Israel Oncology Center (1989–2010) - Moshe E. Stein; Karen Drumea; Tomer Charas; Anthony Gershuny; Rahamim Ben-Yosef (Rambam Maimonides Medical Journal, 2014)
Objective: Over the past 30 years, great strides have been made in the treatment of disseminated testicular tumors. Despite the low number of patients and the rarity of studies concerning primary advanced seminoma, the efficacy of chemotherapy is clear, mainly 3–4-cisplatin-based chemotherapy. Aiming to contribute to the understanding and implementation of proper chemotherapeutic management in advanced seminoma patients, we retrospectively summarized our experience with 26 patients who were referred for platinum-based chemotherapy, post-orchiectomy to the Northern Israel Oncology Center between 1989 and 2010. Response rate, side effects, and long-term outcome were investigated.